Resistência última de navios e plataformas danificados por colisões - Amante, Diogo do Amaral Macedo (2017)
Extreme events may lead to a structural element experiencing a loading scenario above a critical limit known as ultimate strength. This structural failure, in some cases, can develop into the progressive collapse of other structural elements and generate catastrophic consequences. Offshore collisions increase the risk of extreme failure. With increasing demand for safety at sea and protection of the environment, there is a strong interest in predicting the consequences of ship collisions for preventing and minimizing damage to structures and the environment. The severity and potential of accidents with offshore collisions in terms of financial and environmental loss show the great importance of evaluating collision scenarios and the consequences of these accidents. The thesis investigates the ultimate strength and progressive collapse of ships and platforms damaged by collisions using the finite element method. Collision analysis and subsequent verification of residual resistance is a complex, highly nonlinear process and, mainly, involves large plastic deformations. To assess the severity of the damage, there is a need to develop robust and reliable numerical models. Consequently, experimental tests were performed with reduced intact and damaged models of stiffened panels and box girders. Results are expected to increase understanding of structural failure mechanisms, considering damages ranging from small dents to extensive damage to a large area of a ship's hull or FPSO-type platform.